Ice thickness distribution and hydrothermal structure of Elfenbeinbreen and Sveigbreen, eastern Spitsbergen, Svalbard - Navarro Valero, Francisco José; Moeller, Rebecca; Vasilenko, Evgeny; Martín Español, Alba; Finkelnburg, Roman; Möeller, Marco (Journal of Glaciology, 2015)
In recent decades, Svalbard glaciers have been widely radioecho sounded. The earliest extensive surveys of ice thickness were the airborne echo soundings carried out in the 1970s and 1980s (Macheret and Zhuravlev, 1982; Dowdeswell and others, 1984). These studies used low-accuracy radar and positioning systems and mostly consisted of a single profile along the centre line of each glacier. Subsequent radar campaigns, mostly ground-based but sometimes also airborne, used increasingly improved radar and positioning systems providing a wider coverage of the glacier surfaces by radar profiles. A complete summary of glaciers on Svalbard with readily available radio-echo sounded ice-thickness data can be found in Martín-Español and others (2015).